Mesenchymal Stem Cells May Ameliorate Nephrotic Syndrome Post-Allogeneic Hematopoietic Stem Cell Transplantation-Case Report - Zhang, Xin; Peng, Yanwen; Fan, Zhiping; Zhao, Ke; Chen, Xiaoyong; Lin, Ren; Sun, Jing; Wang, Guobao; Xiang, AndyPeng; Liu, Qifa (Frontiers in Immunology, 2017)
Introduction: Because of their immunomodulatory and anti-inflammatory effects , Mesenchymal stem cells (MSCs) have been considered as potential therapeutic agents for treating immune-related or autoimmune diseases, such as graft-versus-host disease (GVHD). Nephrotic syndrome (NS) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an uncommon complication with unclear etiology and pathogenesis. It may be an immune disorder involving immune complex deposition, B cells, regulatory T cells (Tregs) and Th1 cytokines and be a manifestation of chronic GVHD (cGVHD). Corticosteroids and calcium antagonists, alone or in combination, are the most common therapeutic agents in this setting. Rituximab is commonly administered as salvage treatment. However, treatment failure and progressive renal function deterioration has been reported to occur in approximately 20% of patients in a particular cohort. Case presentation: We present a patient who developed NS 10 months after allo-HSCT. After treatment failure with cyclosporine A (CsA), prednisone and rituximab, she achieved a complete response with MSC treatment. The clinical improvement of this patient was accompanied by a decreased B cell population together with an increased frequency of regulatory B cells (Bregs) and Tregs after MSC treatment. Conclusion: MSCs could modulate NS after allo-HSCT by suppressing B cell proliferation, inducing Tregs and Bregs, and inhibiting inflammatory cytokine production by monocytes and NK cells. Among all these, Bregs might play an important role in ameliorating the NS of this patient.